Mídias sociais e transparência : uma análise dos maiores municípios brasileiros - Rocha Junior, Felipe Roberto (2017)
The purpose of this study is to evaluate the relationship between the use of social media by the most populous municipalities in Brazil and the level of public transparency. The adoption of social media around the world has been positively seen as bringing benefits to the public sector, including increased public transparency. However, there are evidences that has identified the use of media as an opportunity for personal and institutional promotion above the increase of public transparency. This paper seeks to fill this gap in the Brazilian environment from the perspective of the Institutional Theory that presupposes the search for legitimacy of organizations through the adoption of socially accepted practices. The characteristics of social media were verified through the analysis of presence, contents of dissemination and interactivity through social media and Web 2.0 tools. The study sample consisted of 98 municipalities among the 100 most populous in Brazil. The survey was conducted with the MPF Transparency Ranking to measure public transparency and the Web 2.0 Disclosure Index to measure the use of social media in Brazilian municipalities. The findings show that the use of social media is at a high stage, but there is little use of Web 2.0 tools. The most publicized content refers to social services, news from the municipality and cultural and sports events. No positive relationship was found between MPF's public transparency and the Web 2.0 Disclosure Index. Negative relationship was found between content posted on Facebook pages and transparency. It is possible that municipalities with low legal transparency are trying to legitimize themselves by disseminating diversified content through social media. It is hoped that the findings of this research motivate other researchers to investigate the effects of the use of social media in the Brazilian context.